Changes of Small Non-coding RNAs by Severe Acute Respiratory Syndrome Coronavirus 2 Infection - Wu, Wenzhe; Choi, Eun-Jin; Wang, Binbin; Zhang, Ke; Adam, Awadalkareem; Huang, Gengming; Tunkle, Leo; Huang, Philip; Goru, Rohit; Imirowicz, Isabella; Henry, Leanne; Lee, Inhan; et al. (Frontiers in Molecular Biosciences, 2022)
TThe ongoing pandemic of coronavirus disease 2019 (COVID-19), which results from the rapid spread of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is a significant global public health threat, with molecular mechanisms underlying its pathogenesis largely unknown. In the context of viral infections, small non-coding RNAs (sncRNAs) are known to play important roles in regulating the host responses, viral replication, and host-virus interaction. Compared with other subfamilies of sncRNAs, including microRNAs (miRNAs) and Piwi-interacting RNAs (piRNAs), tRNA-derived RNA fragments (tRFs) are relatively new and emerge as a significant regulator of host-virus interactions. Using T4 PNK‐RNA‐seq, a modified next-generation sequencing (NGS), we found that sncRNA profiles in human nasopharyngeal swabs (NPS) samples are significantly impacted by SARS-CoV-2. Among impacted sncRNAs, tRFs are the most significantly affected and most of them are derived from the 5’-end of tRNAs (tRF5). Such a change was also observed in SARS-CoV2-infected airway epithelial cells. In addition to host-derived ncRNAs, we also identified several small virus-derived ncRNAs (svRNAs), among which a svRNA derived from CoV2 genomic site 346 to 382 (sv-CoV2-346) has the highest expression. The induction of both tRFs and sv-CoV2-346 has not been reported previously, as the lack of the 3’-OH ends of these sncRNAs prevents them to be detected by routine NGS. In summary, our studies demonstrated the involvement of tRFs in COVID-19 and revealed new CoV2 svRNAs.